Cephalometric evaluation of Class III malocclusion by a modified TweedMerrifield analysis - Mayury Kuramae; Maria Beatriz Borges de Araújo Magnani; João Sarmento Pereira Neto; Darcy Flávio Nouer; Paulo Roberto Aranha Nouer (Universidade Estadual de Campinas, 2015)
A sample of cephalograms of 20 White Brazilian subjects (9 males, 11 females) of 17-36 years old, who presented Class III dental malocclusion was selected and traced. Results showed statistically significant differences among genders for FMIA, SNA, SNB, 1.NB, PFH, AFH, 1-NB and mandibular length. Anteroposterior jaw relation, as shown by SNA and SNB, presented a maxilla correctly positioned, as well as mandibular protrusion, which was related to a normal upper jaw length and an augmented lower jaw length. A vertical growth pattern prevailed, as evidenced by FMA, AFH, PHF and OCC.PL. Angle. The Z Angle, total chin and upper lip failed to clearly show any disturbance of facial esthetics and IMPA, 1.NA, 1- NA, 1.NB and 1-NB revealed dental compensation.